(untitled) (Fiep Bulletin - online, 2011)
Several studies attempt to relate aspects of growth, development and maturation with sports performance specially in search of young people with differentiated motor skills. This study aimed to evaluate somatomotor indicators and fitness related to motor performance of young people. The study is characterized as a descriptive-exploratory one, with a quantitative field approach. We evaluated 31 young, feminine-14 (FEM) (16,14±0,77 years) and 17 masculine-(MASC) (16,12±0,78 years) participants of a sports-social project. To evaluate the physical components resort to battery evaluation proposed by PROESP-BR, being added the analysis of body composition. It was made a database in Microsoft Excel 2007 for Windows ®, to analyze the results we resort to descriptive statistics and inferential statistics with "U" test of Mann Whitney always with a=5,00%.The relative adiposity presented FEM group (28,13%±3,98%) and the MASC (17,9%±6,29%), being the male group rated as great. In the neuromuscular components results were: flexibility (FEM= 30.18±13.10; MASC= 31,88±8,53), strength / abdominal resistance (FEM= 22,14±7,52; MASC= 30,59±9,49), MMII strength (FEM= 157,74±16,75; MASC= 199,09±18,55) and MMSS (FEM=320,71±39,85; MASC= 435,29±69,88); agility (FEM= 06,99±00,70; MASC= 06,05±00,40), speed (FEM= 04,24±00,53; MASC= 03,56±00,40). In general resistance results were: (FEM= 1220,97±170,62; MASC= 1600,36±175,56). Our results do not differ from the literature, but we can not regard them as satisfactory, because young people surveyed are participants in physical and sports activities regularly. These projects that aimed the engagement of young people in physical and sports activities should seek to encourage the improvement of health, not just the improvement of motor performance. It is suggested that other studies are conducted with students and practitioners of other activities.